Em viagem: sobre outras paisagens e movimentos no romance contemporâneo - Maria Isabel Edom Pires (Estudos de Literatura Brasileira Contemporânea)
On the different dislocations of some protagonists in Brazilian literature, we may highlight, in João Gilberto Noll‟s novel Lorde , some aspects which vary in gradation, such as the consciousness of exile, the experience between two words and the contact wi th clandestinity. Characters which travel in the novels Algum lugar , by Paloma Vidal; Azul - corvo , by Adriana Lisboa; and Estive em Lisboa e lembrei de você , by Luiz Ruffato, also point out to those motivations, embodying the contemporary migration and indi cating diverse cultural maps. We aim to question about the convergence points between these novels, pondering on how Brazilian literature is thinking about traveling from some fundamental moments of its constitution.